REPRESENTASI NILAI MORAL PADA FILM “AGAK LAEN” KARYA BENEDION RAJAGUKGUK (KAJIAN SOSIOLOGI SASTRA) - Vahlevi, Muhammad Reza; Puspitasari, Indah (Universitas Islam Zainul Hasan Genggong, 2024)
This research aims to study and find representations of moral values ​​contained in the film